Method optimization and validation for the routine analysis of multi-class pesticide residues in Kinnow Mandarin and fruit quality evaluation. (1st February 2022) - Bibi, Aasma; Rafique, Nazia; Khalid, Sofia; Samad, Abdul; Ahad, Karam; Mehboob, Farrakh
Graphical abstract: Highlights: Citrate-buffered extraction with PSA-C18 clean-up was found suitable for Kinnow Mandarin. Status of pesticide residues from the country's top 22 Kinnow Mandarin exporting units, was evaluated. Calculated IqR, which is a useful tool for segregating the good and bad quality fruits. Strict regulations are required to control the use of banned pesticides in food production. Abstract: The present study describes the selection of a sensitive multi-residue method that can be used for the routine testing of pesticides in Kinnow Mandarin. The citrate-buffered QuEChERS extraction followed by primary secondary amines and C18 clean-up was found suitable for the analysis of fifty four pesticides. The limit of quantification for the selected pesticides was lower than maximum residue limits (MRLs) set by European Union, Codex Alimentarius Commission (CAC), and twelve other countries. The method's accuracy ranged from 74.4 to 112% and expanded uncertainty ranged from 7.5 to 49.6%. The validated method was applied to Kinnow Mandarin samples, collected from 22 export units of district Sargodha, Pakistan. Almost 27% of the samples (n = 22) were exceeding the CAC-MRLs. The index of quality for residues (IqR), for 64% of the samples, was considered adequate. The study indicates the need for regular monitoring to protect public health and ensure safe and consistent trade.